Pengaruh Kualitas Pelayanan, Kepercayaan, dan Citra Merek Terhadap Kepuasan Konsumen - Salma Yudita Pratiwi; Meylani Tuti (LPPM Universitas Asa Indonesia, 2022)
This study aims to analyze the effect of service quality, trust, brand image on consumer satisfaction. The population in this study are consumers who use the Jakarta Explorer Tour bus. The sampling technique used is purposive sampling, namely respondents who use the Jakarta Explorer Tour bus who have done it more than twice and obtained a total sample of 200 people. To test the proposed hypothesis, this study uses the (Partial Least Squares- Structural Equation Modeling) PLS-SEM. The PLS SEM analysis was carried out in two stages in 2 sessions. The initial stage is an analysis of reliability and validity, while the second session is the estimation and leveraging of the path coefficients and power of the structural model. This research uses the help of software SmartPLS 3.2.9. The results of this study indicate that there is a direct positive between brand image and trust on consumer satisfaction and an indirect effect of service quality on customer satisfaction.